Family attitude and responsibility: A Quranic-based theoretical framework in the globalization challenges - Qomaro Galuh Widitya; Supaat Dina Imam; Nasrulloh Nasrulloh (BIO Web of Conferences, 2024)
This study addresses the urgent need for a theoretical framework on family attitudes and responsibilities in Islam, particularly in response to the challenges posed by globalization that threaten traditional Muslim family values. The research contribution is the development of a new theoretical model that integrates emotional well-being, spiritual leadership, and the balance of rights and responsibilities, based on Quranic teachings. The methodology involved a textual analysis of Quranic verses to formulate variables and indicators related to family attitudes and responsibilities, followed by a survey to evaluate the instrument's validity and reliability. The results demonstrate a strong correlation between spiritual leadership and family harmony, highlighting emotional well-being as a key factor in maintaining a sakinah (peaceful) family. The study finds that the balance of rights and responsibilities rooted in Islamic principles significantly contributes to family stability. This framework serves as a foundational tool for future research on Muslim family development. Future studies should test the model empirically across different cultural contexts to ensure its applicability.